2015
DOI: 10.1007/s12011-015-0403-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium on the Levels of Cytokines and Trace Elements in Toxin-Mediated Oxidative Stress in Male Rats

Abstract: Selenium is an essential cofactor in the key enzymes involved in cellular antioxidant defense. This study was designed to investigate the protective effects of selenium on mercury chloride (HgCl2)-induced toxicity. Male Wistar rats were randomly divided into four groups of six animals each. The first group was control; the second group was treated with mercuric chloride (HgCl2: 50 mg/kg/bw). The third group was treated with sodium selenite (Se 0.2 mg/kg/bw), and the fourth group received Se (0.2 mg/kg/bw) plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…It has been shown that selenium plays an important role in the continuation of the physiological functions of the nervous system (such as signal transduction and development) (10). Previous studies have shown that selenium has a neuroprotective role in various experimental pathologies, such as spinal cord injury, cerebral ischemia and neurotoxicity models (11)(12)(13)(14)(15). Similarly, in our previous study, selenium prevented neurotoxicity that was induced by cisplatin in a partial level (16).…”
Section: Introductionsupporting
confidence: 72%
“…It has been shown that selenium plays an important role in the continuation of the physiological functions of the nervous system (such as signal transduction and development) (10). Previous studies have shown that selenium has a neuroprotective role in various experimental pathologies, such as spinal cord injury, cerebral ischemia and neurotoxicity models (11)(12)(13)(14)(15). Similarly, in our previous study, selenium prevented neurotoxicity that was induced by cisplatin in a partial level (16).…”
Section: Introductionsupporting
confidence: 72%
“…Pb can also decrease the level of GSH by inhibiting the activities of GSH metabolizing enzymes, such as GR, GST, and glucose-6-phosphate dehydrogenase, by blocking their SH groups [19]. Our earlier studies have shown protective effect of natural polyphenols and antioxidants on toxin mediated toxicity in vivo [20][21][22]. Extensive research is now focusing on herbal products as alternative medicines and a number of studies showed the beneficial effects of curcumin [23] which undergoes metabolism upon oral administration in animals and almost each and every metabolite produced has some beneficial effect apart from their antioxidant property.…”
Section: Discussionmentioning
confidence: 99%
“…MDA levels are a marker of cellular lipid peroxidation, which indirectly reflects the degree of cell damage [32]. In addition, Ansar et al [33] showed that Se has a protective effect against oxidase activity. In accordance with Toxins 2020, 12, 143 9 of 14 this, we observed that the activity of GSH-Px, T-SOD and T-AOC in the liver of chickens exposed OTA were lower than those in the control group, while MDA levels were higher.…”
Section: Discussionmentioning
confidence: 99%